Trigonometric series with uniformly distributed coefficients - Samoilenko, M. A. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We prove the Hölder condition for the sums of series obtained by the substitution of uniformly distributed sequences for random variables in the Fourier expansion of a wiener process.